Interrelationship between Changes in the Amyloid β 42/40 Ratio and Presenilin 1 Conformation - Katarzyna Marta Zoltowska; Masato Maesako; Oksana Berezovska (BMC, 2016)
Abstract The ratio of the longer (Aβ42/Aβ43) to shorter (Aβ40) species is a critical factor determining amyloid fibril formation, neurotoxicity and progression of the amyloid pathology in Alzheimer's disease. The relative levels of the different Aβ species are affected by activity and conformation of the γ-secretase complex catalytic component presenilin 1 (PS1). The enzyme exists in a dynamic equilibrium of the conformational states, with so-called "close" conformation associated with the shift of the γ-secretase cleavage toward the production of longer, neurotoxic Aβ species. In the current study, fluorescence lifetime imaging microscopy, spectral Förster resonance energy transfer, calcium imaging and cytotoxicity assays were utilized to explore a reciprocal link between the Aβ42 and Aβ40 peptides present at various ratios and PS1 conformation in primary neurons. We report that exposure to Aβ peptides at a relatively high ratio of Aβ42/40 causes conformational change within the PS1 subdomain architecture toward the pathogenic "closed" state. Mechanistically, the Aβ42/40 peptides present at the relatively high ratio increase intracellular calcium levels, which were shown to trigger pathogenic PS1 conformation. This indicates that there is a reciprocal cross-talk between the extracellular Aβ peptides and PS1 conformation within a neuron, with Aβ40 showing some protective effect. The pathogenic shift within the PS1 domain architecture may further shift the production of Aβ peptides toward the longer, neurotoxic Aβ species. These findings link elevated calcium, Aβ42 and PS1/γ-secretase conformation, and offer possible mechanistic explanation of the impending exacerbation of the amyloid pathology.